Australian Contributions to Coconut (Cocos nucifera L.) Research (A Review Article) - Foale, Mike; Adkins, Steve (International Coconut Community Journal, 2014)
Australia has been a significant supporter of research into coconut protection, improvement and biotechnology for three decades. Major achievements include a key role in identification of the Cadang Cadang Viroid in Philippines and the Foliar Decay virus in Vanuatu, surveys of coconut genetic diversity in the south Pacific, and the initiation of global collaboration leading to the formation of the Coconut Genetic Resources Network. Another major Australian contribution beginning in the 1980s, has been to the development and refinement of methods of collection and exchange around the world of diverse coconut genotypes under COGENT involving particularly the protocol for embryo transfer and culture. Most recently CO2 enrichment of the in vitro atmosphere has raised cultured embryo growth to a new level at the University of Queensland (UQ). Researchers at UQ have brought somatic embryogenesis, a critical process for multiplication of high-value individual palms, to the verge of commercial application, has and also greatly advanced the technique for preserving genetic material by cryopreservation of the embryo. The development of a healthy and high-value snack food from coconut kernel has also emerged at UQ. Modest additional funding would advance all of these recent projects to the stage of general application, thereby building on the strong record of Australia in helping to secure the future of coconut producers in the community and economy of Pacific nations, and beyond.